Analisis Status Gizi dan Tingkat Kebugaran Jasmani Atlet Futsal Univeristas PGRI Pontianak - Wibowo, Agus Tri (Journal Sport Academy, 2025)
This study aims to analyze the nutritional status and physical fitness level of male futsal athletes at Universitas PGRI Pontianak. The research employed a quantitative descriptive method with a sample of 18 male futsal athletes selected using purposive sampling. The research instruments included anthropometric measurements using the Body Mass Index (BMI) to determine nutritional status, as well as the bleep test to measure physical fitness levels. Data were analyzed using descriptive statistics to obtain mean values and assessment categories. The results showed that the nutritional status of the male futsal athletes was in the normal category, with an average BMI score of 18.5. Meanwhile, the measurement of physical fitness levels showed an average score of 24.2, which falls into the fairly good category. These findings indicate that although the athletes’ nutritional condition is already within the ideal category, their physical fitness level still requires improvement to reach the good or very good level. Based on these results, it can be concluded that maintaining good nutritional status should be accompanied by a more structured and continuous training program to enhance physical fitness.